Perception of Public Relations Practice Among Selected Chief Executive Officers (CEOs) In Ghana - Isaac Tandoh; Kwame Asare Duffour; Mavis Essandoh; Eric Opoku Mensah (Communicare : Journal of Communication Studies, 2022)
The study's goal was to find out what some of Ghana's top executives thought about public relations. The goals were to determine the Chief Executive Officers' (CEOs') understanding of public relations, as well as their perceptions of public relations' role in strategic management and the restrictions of public relations' role in corporate strategy. Through an in-depth interview with five (5) CEOs of chosen agencies within Ghana's Ministry of Transport, the study gathered data using a qualitative research technique. This data was then evaluated using theme analysis, which demonstrated that the public impression of public relations practice in Ghana is positive, implying that the technique is effective. Public relations were deemed to be an important role in strategic management, particularly if it was part of top management. It also limited its contribution to business strategy owing to a variety of problems experienced in the chosen firms, including financial limits, a lack of deep understanding of CEOs in public relations, and others. According to the conclusions of the research, Ghanaian CEOs and business leaders should identify and promote public relations practice. The Institute of Public Relations Ghana should speed up its attempts to enact a statute making public relations a regulated profession.